Double-stranded RNA bacteriophage phi 6 protein P4 is an unspecific nucleoside triphosphatase activated by calcium ions. - Paatero, A O (1995)
Double-stranded RNA bacteriophage phi 6 has an envelope surrounding the nucleocapsid (NC). The NC is composed of a surface protein, P8, and proteins P1, P2, P4, and P7, which form a dodecahedral polymerase complex enclosing the segmented viral genome. Empty polymerase complex particles (procapsids) package positive-sense viral single-stranded RNAs provided that energy is available in the form of nucleoside triphosphates (NTPs). Photoaffinity labelling of both the NC and the procapsid has earlier been used to show that ATP binds to protein P4 and that the NC hydrolyzes NTPs. Using the NC and the NC core particles (NCs lacking surface protein P8) and purified protein P4, we demonstrate here that multimeric P4 is the active NTPase. Isolation of multimeric P4 is successful only in the presence of NTPs. The activity of P4 is the same in association with the viral particles as it is in pure form. P4 is an unspecific NTPase hydrolyzing ribo-NTPs, deoxy NTPs, and dideoxy NTPs to the corresponding nucleoside diphosphates. The Km of the reaction for ATP, GTP, and UTP is around 0.2 to 0.3 mM. The NTP hydrolysis by P4 absolutely requires residual amounts of Mg2+ ions and is greatly activated when the Ca2+ concentration reaches 0.5 mM. Competition experiments indicate that Mg2+ and Ca2+ ions have approximately equal binding affinities for P4. They might compete for a common binding site. The nucleotide specificity and enzymatic properties of the P4 NTPase are similar to the NTP hydrolysis reaction conditions needed to translocate and condense the viral positive-sense RNAs to the procapsid particle.